Notulae to the Italian flora of algae, bryophytes, fungi and lichens: 19 - Sonia Ravera; Alfredo Vizzini; Annalena Cogoni; Cecilia Totti; Michele Aleffi; Renato Benesperi; Elisabetta Bianchi; Wolfgang von Brackel; Giorgio Buffa; Laura Cancellieri; Antonio B. De Giuseppe; Sofia De Mei; et al. (Italian Botanist)
In this contribution, new data concerning algae, bryophytes, fungi and lichens of the Italian flora are presented. It includes new records, confirmations or exclusions for the algal genera Cladophoropsis, the bryophyte genera Bryum, Cinclidotus, Dicranella, and Pulvigera, the fungal genera Ascocoryne, Calycina, Echinoderma, Hohenbuehelia, Laccaria, Lasiosphaeria, Leucocoprinus, Neodasyscypha, Propolis, Psathyrella, and Sclerococcum, and the lichen genera Acarospora, Bryoplaca, Caloplaca, Candelariella, Catapyrenium, Cladonia, Lecanora, Lepra, Monerolechia, Mycobilimbia, Pertusaria, Pycnora, Spilonema, Thelopsis, and Xylopsora.